Peran dan Tanggung Jawab Notaris Dalam Pembuatan Akta Perkawinan Campuran - Tifonia Tionusa; Arsin Lukman (Faculty of Law, University of Mataram, 2023)
Globalization have push marriage to be perform not only between Indonesian citizens but also may be done with foreigners. As it is known, through marriage could pooling the assets between the spouses which leads to the matter of ownership in the property whereas Indonesians cannot own land and buildings in Indonesia. Therefore, notary has a role in making authentic deed under the form of mixed marriage or also known as mixed marriage agreement. The purpose of this study is to examine and analyze the roles and responsibilities of a notary in making mixed marriage deeds. This study uses a normative legal research method with a statutory approach, presenting cases in the form of decisions, and analysis. The results shows that there are problems related to the making of a mixed marriage deed made by a notary. These problems are in the form of a notary who does not provide legal counseling on the deed that the clients want to make (Indonesian citizens and citizens of a foreign country), does not translate or explain the deed if it appeared not understandable, and does not write it down at the end of the deed that a translation or explanation has been carried out because the present does not understand the language used written in the deed. In addition, with these problems, the strength of proof and the legal consequences of the act made by the notary are affected. Therefore, notaries in carrying out their positions must be guided by Notary Department Law.